2021
DOI: 10.1192/bjo.2021.59
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective examination of care pathways in individuals with treatment-resistant depression

Abstract: Background Individuals with treatment-resistant depression (TRD) experience a high burden of illness. Current guidelines recommend a stepped care approach for treating depression, but the extent to which best-practice care pathways are adhered to is unclear. Aims To explore the extent and nature of ‘treatment gaps’ (non-adherence to stepped care pathways) experienced by a sample of patients with established TRD (non-response to two or more adequate treatments in the current depressive ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The UK: One study of MDD-diagnosed participants identified a referral rate of 21% to secondary care over 3 years, [43], although rates as low as 5 and 6% [63, 75] have been reported. One study of people with TRD identified a rate of 44%, but acknowledged a likely overestimation [55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The UK: One study of MDD-diagnosed participants identified a referral rate of 21% to secondary care over 3 years, [43], although rates as low as 5 and 6% [63, 75] have been reported. One study of people with TRD identified a rate of 44%, but acknowledged a likely overestimation [55].…”
Section: Resultsmentioning
confidence: 99%
“…Patient variability: Certainly, the characteristics of patients included in the studies reviewed impact the extent of treatment gaps. Those with more severe depression are more likely to receive diagnosis, treatment, follow-up, and specialist care [55]. As such, if we had limited our synthesis to those with moderate or severe depression, the treatment gaps would likely have been much smaller, although the quantity of evidence would have been much smaller.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another one is not starting adjunctive therapies such as lithium and atypical antipsychotics after two unsuccessful antidepressant trials, which again confirms the great need for improvement in the treatment of TRD. The authors also point out the lack of guideline standardization concerning the sequence, the number of steps, and the assessment of the best moment to go to another step [ 27 ]. The progressive course of TRD is presented graphically on Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Both lithium and quetiapine are recommended by most major treatment guidelines ( Taylor et al, 2020 ), but the existing evidence does not favour one over the other, leading to clinical equipoise ( Bauer et al, 2013 ). However, despite evidence of efficacy and guideline recommendations, augmentation is underused in clinical practice and there remains a proportion of patients who do not find augmentation adequately helpful ( Day et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%